Social Moral Education Values in Akhlak Lil Banin for Islamic Religious Learning within Multicultural Societies - Dhea Arianti; Agus Pahrudin; Ida Faridatul Hasanah (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Indonesia's multicultural society demands that Islamic Religious Education (PAI) move beyond cognitive mastery toward internalizing social moral values that foster inclusive, tolerant, and harmonious attitudes. However, current PAI practices often emphasize normative memorization over systematic social-moral integration, which limits students' ability to apply these values in real-life multicultural interactions. This study identifies and classifies the social moral values in Akhlak Lil Banin Volume I and examines their significance to PAI within a multicultural framework. Using a qualitative library research design and content analysis, this study examines Chapters 12, 15, 30, 31, and 32 of the text. The findings reveal a structured and substantive framework consisting of six core values: respect for parents, etiquette toward teachers, solidarity among peers, polite communication, personal responsibility, and social discipline. These values create a relational ethical framework that promotes harmony among groups and are very similar to the core competencies of PAI. The study finds that pedagogical strategies such as role modelling, habituation, and moral reflection can effectively integrate these values. Ultimately, Akhlak Lil Banin serves as an applicable pedagogical reference that strengthens students' religious dimensions while contributing significantly to social harmony in a pluralistic society.